Keteladanan Rasulullah dalam PendidiKan Berkarakter - A. Rahman Ritonga (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
Rasulullah is the recommended figure of God as a model of good behavior. His behavior in various aspects of life is acceptable, not only by muslims but also by non muslim. Rasulullah has a complete and perfect characters. Each of nature and practice of his life that recorded by historians is filled by positive messages for character development of muslims. If Muslims in his age and his companions age have the power of moral, religious and economi aspect, it is because they made Rasullah as a model of good life. After that generations, Muslims are no longer interested in imitation of the Prophet life style. Among their reasons is that the Prophet’s lifestyle that recorded in the history and traditions of the Hadith is only relevant to that era. Now the times and circumstances have changed, they regard that applying of the Prophet’s life style is not relevant anymore. Therefore, they argue that by following the Prophet’s lifestyle would lead them to underdevelopment. This perception was clearly misleading, because moving of the present time to the past is impossible, but the attitude and behavior of the Prophet’s life was formed by God that remains relevant actualized in every age and in all aspects, including character education aspect.